Novel Surgical Treatment for Refractory Heel Ulcers in Werner’s Syndrome - Keisuke Oe; Masahiko Miwa; Yoshitada Sakai; Masahiro Kurosaka (Case Reports in Orthopedics)
Patients with Werner’s syndrome frequently develop chronic leg ulcers that heal poorly. We present a patient who suffered from this rare syndrome and developed typical heel ulcers. Treatment of the ulcer is challenging, as flap options are limited over the lower third of the leg and skin grafting is not easy as there is a lack of healthy granulations. We successfully treated the ulcer with osteomyelitis by drilling the bone and applying an ultrathin split thickness skin graft with the thigh skin as the donor site.